Improving News Listening Ability Using Cooperative Learning Model Type Talking Stick - Serwunan, Marco; Sasabone, Carolina; Parinussa, Jolanda Dessye (Universitas Pattimura, 2023)
Improved ability to listen to the news using learning models talking stick type cooperative class VII-7 SMP Negeri 7 Ambon. Thesis. Indonesian Language and Literature Education Study Program, Department of Language and Arts, Faculty of Teacher Training and Education, Pattimura University. Classroom action research is Classroom action research conducted in class with the aim of improving and enhancing the quality of learning practices. This study aims to describe Improved ability to listen to the news using learning models talking stick type cooperative class VII-7 SMP Negeri 7 Ambon. This research includes the type of classroom action research. The techniques used in data collection, questionnaire interviews. The instruments used were observation sheets, interviews, documentation questionnaires. The subjects of this study were Class VII students of SMP Negeri 7 Ambon with a total of 207 students however, the researcher only took one class as a source of research, namely class VII-7 which consisted of 22 students. The results of research analysis, data analysis can be concluded that the increase in the ability to listen to the news using a learning model cooperative talking stick type can improve quite well, these is in accordance with the data obtained in the first cycle of 60, 18% and can be increased in the second cycle of 80,63% which is good.